2002
DOI: 10.1074/jbc.m201563200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor of Activated T Cells Is a Driving Force for Preferential Productive HIV-1 Infection of CD45RO-expressing CD4+ T Cells

Abstract: Human immunodeficiency virus type-1 (HIV-1) preferentially replicates in CD4-expressing T cells bearing a "memory" (CD45RO؉) rather than a "naive" (CD45RA؉/ CD62L؉) phenotype. Yet the basis for the higher susceptibility of these cells to HIV-1 infection remains unclear. Because the nature of the CD45 isoform itself can affect biochemical events in T cells, we set out to determine whether these isoforms could differently modulate HIV-1 long terminal repeat (LTR) activity and thereby replication. Through the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 66 publications
1
20
1
1
Order By: Relevance
“…44 Antibodymediated engagement of the TCR/CD3 complex and host-cell attachment by HIV-1 virions ectopically expressing CD86 can synergize to activate NFAT-stimulated HIV-1 LTR transcription. 45 Also, consistent with the previous finding that NFAT levels are upregulated in memory/effector CD4T cells, 11 NFAT1 was recently identified as a major factor responsible for the preferential replication of HIV-1 in CD45RO þ 'memory' T lymphocytes, 46 a potential reservoir of latently infected cells. Interestingly, NFAT-driven HIV-1 LTR transcription Method by which the effect of this site was examined.…”
Section: Nfat and Hiv-1 F Pessler And Rq Cronsupporting
confidence: 78%
“…44 Antibodymediated engagement of the TCR/CD3 complex and host-cell attachment by HIV-1 virions ectopically expressing CD86 can synergize to activate NFAT-stimulated HIV-1 LTR transcription. 45 Also, consistent with the previous finding that NFAT levels are upregulated in memory/effector CD4T cells, 11 NFAT1 was recently identified as a major factor responsible for the preferential replication of HIV-1 in CD45RO þ 'memory' T lymphocytes, 46 a potential reservoir of latently infected cells. Interestingly, NFAT-driven HIV-1 LTR transcription Method by which the effect of this site was examined.…”
Section: Nfat and Hiv-1 F Pessler And Rq Cronsupporting
confidence: 78%
“…Independent studies have shown that selective NFAT activation produces a phenotype similar to that of EC stimulation in HIV-infected T cells. NFAT-driven HIV production leads to preferential infection of memory T cells (50), and viral replication occurs without T-cell proliferation, activation marker expression, or cytokine expression (26). Lastly, selective NFAT activation, like HIV replication in our system, can be augmented by EC-specific factors.…”
Section: Discussionmentioning
confidence: 98%
“…It is well-known that HIV-1 replicates preferentially in effector and memory CD4 ϩ T cells and cells displaying a naive phenotype do not support virus gene expression (51). This inability to allow virus replication seems to be linked with the absence of NFAT in naive CD4 ϩ T cells (65,(67)(68)(69). It was previously demonstrated that NFAT acts in synergy with NF-B to promote HIV-1 replication in activated and memory CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%